2007
DOI: 10.1016/j.cardiores.2006.11.033
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine attenuates PKCβ2overexpression and myocardial hypertrophy in streptozotocin-induced diabetic rats

Abstract: The results suggest that PKCbeta(2) overexpression represents a mechanism causing hyperglycemia-mediated myocardial hypertrophy, which can be prevented by the antioxidant N-acetylcysteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 39 publications
9
75
1
Order By: Relevance
“…Enhanced MDA and ROS were accompanied by compromised Mn-SOD activity, GSH content and total antioxidant concentration. These findings are similar to those reported in the previous literature (22,30), indicating increased levels of oxidative stress in diabetic rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Enhanced MDA and ROS were accompanied by compromised Mn-SOD activity, GSH content and total antioxidant concentration. These findings are similar to those reported in the previous literature (22,30), indicating increased levels of oxidative stress in diabetic rats.…”
Section: Discussionsupporting
confidence: 93%
“…One wk after diabetes induction, NAC and α-LA were administered to the diabetic treated groups by oral gavage for eight wks. The concentrations of NAC and α-LA were adjusted for a daily intake of 1.4 g/kg and 60 mg/kg, respectively, according to previous studies (22,23).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Taking this into consideration, NAC treatment aiming at reduced MDA levels represents a promising therapeutic opportunity. But, in spite of many reports reassuring its beneficial effect on oxidative stress (22,(32)(33)(34), our study has failed to reduce MDA concentrations. We do not have a clear understanding about the reason why NAC treatment did not restore normal MDA levels, but we hypothesize that this failure could be related to NAC dose or late onset of NAC treatment.…”
Section: Discussioncontrasting
confidence: 63%
“…Of these, 8-iso-prostaglandin F 2 (8-iso PGF 2 ) has recently been shown to be a specific and sensitive quantitative index of oxidative stress in vivo (Delanty et al, 1997). We and others have found that in STZ rats with type 1 diabetic cardiomyopathy, LV levels of 8-iso PGF 2 were significantly increased in vivo (Hamblin et al 2007a(Hamblin et al , 2007bXia et al, 2007). Collectively, these experimental animal studies demonstrate that diabetic cardiomyopathy is associated with greater myocardial oxidative stress burden.…”
Section: Myocardial Oxidative Stress: a Key Contributor To Diabetic Csupporting
confidence: 51%